Yerevan During the Arab Invasions in the 50s of VII century - Yeghiazaryan, Arman (History and Culture, 2022)
In the 7th century, Yerevan, becoming an urban settlement, developed as a fortress city on a large transit highway. On the other hand, it was of great strategic importance to the Arabs who aspired to dominance in the region in the middle of the century. In connection with all this, the influence of Yerevan in the political life of Armenia and in the struggle against foreign invaders increased. As of the 750s, a fierce battle or fight took place in Yerevan, which is mentioned by Hovhannes Draskhanakertsi and Samvel Anetsi, referring to Asogik and Shapuhi, who told about it in detail. However, no information was preserved in the work of Asoghik, and the history of Shapukh has disappeared; so the researchers made only assumptions about the content of the time of the “Battle of Yerevan”. Some identify the "Battle of Yerevan" with the failed siege of the Yerevan fortress by the Arabs in 650, others separate these two events. The study of new sources makes it possible to clarify that the "Battle of Yerevan" took place during the Arab invasion in 655, when the Arab troops in the Yerevan region carried out several operations in different directions, capturing all the local settlements and fortresses. Judging by the sources, Yerevan was eventually captured by the Arab army, but after a long struggle, which differed from the logic of the conquest of other parts of the region in its character and extent, therefore it was singled out by historians and called the “Battle of Yerevan”.
Keywords: Battle of Yerevan; Arab invasion; siege; Hovhannes Draskhanakertsi; Samvel Anetsi; Persian-Byzantine border; fortified city; route; capture; sources